EDUKASI PENTINGNYA MELAKUKAN PEMERIKSAAN GOLONGAN DARAH DI SB JALAN KEBUN SELANGOR MALAYSIA - Bastian, Bastian; Ulva, Maria; Yuniasari, Widya; Suratun, Suratun; Yasmin, Sri (Jurnal Abdi Insani, 2024)
Blood is the most important part of the body of living things. Blood circulates in the heart and blood vessels throughout the body carrying oxygen and nutrients. Types of blood tests performed include hemoglobin levels, blood cell count, hematocrit, ESR, erythrocyte index, hemostasis, blood type, diffcount (leukocyte count). One of the blood components circulating in the body that functions to transport oxygen and nutrients needed by cells is red blood cells (erythrocytes). On the surface of the red blood cell membrane there is a protein that determines the type of blood type. Blood type is a blood classification system based on the type of antigen it has. There are two most important types of blood types, namely A-B-O and Rhesus (Rh Factor). Blood transfusion from incompatible blood types can cause immunological transfusion reactions that result in hemolytic anemia, kidney failure, shock, and even death. Many people do not yet know the importance of blood type testing. Therefore, it is necessary to carry out socialization and education with the aim of increasing knowledge and understanding regarding the importance of blood type testing. The media used related to the Education on the Importance of Blood Type Checks is socialization and education through poster media, as well as demonstrations at the end of the activity